Korean Wave sebagai Instrumen Soft Power untuk Memperoleh Keuntungan Ekonomi Korea Selatan - Suryani, Ni Putu Elvina (UI Scholars Hub, 2014)
Korean wave is a term used to illustrate the product of South Korean pop culture that has been successfully exported to foreign countries in Asia, Europe, and America. By using the concept of 'soft power', this article argues that, while this phenomenon merely seems like an entertainment phenomenon, Korean wave has actually become a vital instrument that brings positive impacts towards the economic development of South Korea. The strategy to develop the Korean wave as a soft power instrument is actually something that Indonesia must be able follow. This might be useful as an alternative strategy to optimize the role of Indonesian local culture as an effort to drive the national economy in order to face the current global challenges.